Validation and Psychometric Testing of the Chinese Version of the Mental Health Literacy Scale Among Nurses - Wang, Anni; Jia, Shoumei; Shi, Zhongying; Sun, Xiaomin; Zhu, Yuan; Shen, Miaoli (Frontiers in Psychology, 2022)
Abstract: The Mental Health Literacy Scale (MHLS) is the most widely used and strong theory-based measurement tool to gain an understanding of mental health knowledge and ability. This study aimed to test the psychometric properties of the Chinese version of the Mental Health Literacy Scale (MHLS-C) and to document the norm and its influential factors of mental health literacy among nurses. The MHLS was translated following Brislin’s translation model and tested with a sample of 872 clinical registered nurses. The Jefferson Scale of Empathy-Health Professionals (JSE-HP), Patient Health Questionnaire-2 (PHQ-2), and Generalized Anxiety Disorder-2 (GAD-2) were administered to assess convergent validity. The minimum average partial test , parallel analysis and confirmatory factor analysis supported 4 first-order 2 second-order structure. The 4 factors were named ‘knowledge of mental disorder’, ‘ability to seek information and help’, ‘recognition of mental disorder’, and ‘acceptance of patients with mental illness’, with factor 1-3 were summarized into MHLS-Core (Core literacy subscale) and factor 4 as MHLS-SA (Social acceptance subscale). The MHLS-C was moderately negatively correlated with the PHQ-2 and GAD-2 (-0.111, -0.081) and highly positively correlated with JSE-HP (0.492). The Cronbach’s α was 0.85 for the overall scale and 0.89 and 0.93 for two subscales. The test-retest reliability was good, with intraclass correlation coefficients (ICCs) of 0.80 for the whole scale, and0.79 and 0.94 for two subscales. As an approximately normal distribution, the 50th percentile for the MHLS-C was 99, with 50th percentiles of 74 and 20 for MHLS-Core and MHLS-SA. Higher position, higher professional credentials, higher hospital hierarchy, other specialist hospital, psychiatric hospital and unmarried status were positive predictors. The 29-item MHLS-C, with two subscales of MHLS-Core and MHLE-SA, is a stable and validated tool to measure mental health literacy. MHLS-Core could be used independently to measure the core content of mental health literacy. It may be applicable for Chinese health professionals, but need further validation among the general public. MHL curriculum and a targeted culturally appropriate program for acceptance for health professionals, especially for those in general hospitals and with less working tenure, may be recommended.